CFD simulation of heat transfer in vertical ribbed tube - Sasi Koshad, Rabi Abrahim (2011)
Computational Fluid Dynamics (CFD) simulation of heat transfer and fluid flow analysis in the turbulent flow regime in a spirally ribbed tube and a smooth tube in vertical orientation are presented in this thesis. The ribbed tube has outside diameter of 25mm, maximum inner diameter of 18.80mm, minimum inner diameter of 17.50mm and helix angle of 60o .The smooth tube has outside diameter of 26.7mm and inner diameter of 18.88mm. Both tubes were uniformly heated by passing an electrical current along the tube with a heated length of 1000mm. The CFD simulation was conducted on a vertical orientation of the steel tubes (rifled and smooth) under six different inlet velocities of 0.893m/s, 1.786m/s, 2.38m/s, 2.976m/s,3.57m/s and 4.166m/s. The objective of this thesis is to determine the heat transfer and pressure drop in both vertical smooth and ribbed tubes. The fluid used is water and the initial temperature is 25oC. The heat flux that for heating the tube is equal to 150KW/m2 . During the CFD simulation analysis it was found that for smooth tube at lower inlet velocity, the temperature increases from 2980K to 307.50K while the pressure drop between inlet and outlet is equal to 741.34 Pa. At higher inlet velocity, the temperature for smooth tube is found increasing from 2980K to 3000K, with the pressure drop is equal to 9402.44 Pa. For the ribbed tube at lower inlet velocity the temperature is increasing from 2980K to 308.50K, with the pressure drop is found to be 1655.5 Pa. In the case of a higher inlet velocity, the temperature increase in ribbed tube is increasing from 2980K to 300.40K, while the pressure drop is equal to 23166.5 Pa. It is clear that the temperature difference between ribbed and smooth tube at lower inlet velocity are equal to 10.190K and 9.270K, respectively. While at higher inlet velocity their, temperature difference become 2.2 0K, and 1.8 0K respectively. At the heat flux equal to 300KW/m2 and inlet velocity equal to 0.893 m/s, the temperature difference between ribbed and smooth tubes are 21.010K and 17.950K respectively. This result indicates that the ribbed tube has higher heat transfer efficiency than the smooth tube. The pressure drop in the ribbed tube is also found to be less than that of the smooth tube. This clearly shows that the characteristic of ribbed tube is much better than smooth tube. Thus the ribbed tube is able to enhance the heats transfer capability for fluid flow in the tube